Economic Distress and Suicide - Dyg Affizzah, A.M.; Nur Shafiena, Sidik (HRMARS, 2020)
This research aimed to study the nexus between the economic crises and commit suicide of the G7 countries by using a panel data approach. In this study, the variables collected are the number of suicides (SUICIDE), Gross Domestic Product per capita (PCGDP), the number of unemployed (UNEMP), the alcohol consumption per capita (ALC) and the fertility rate (FERT) were collected. This research adopted various tests such as the Ordinary Least Square (OLS) Regression model, Random-Effects model, Fixed-Effects model, Breusch-Godfrey Lagrange multiplier and Hausman test to analyse the data collected. The results of the analysis show that the UNEMP is positively correlated to the number of suicides while the FERT is negatively correlated to the number of suicides. Onthe other hand, the PCGDP and ALC do not affect the number of suicides significantly which implied that the PCGDP and ALC have a mix relationship with the number of suicides. In short, the UNEMP and FERT are the leading factors that affect the number of suicides in the G7 countries.